Effects of cathode rotation and substrate materials on electrodeposited CoMnP thick films. (29th January 2021) - Wu, Chun-Wei; Lin, Chiao-Chi; Chin, Tsung-Shune; Chang, Jen-Yuan; Sung, Cheng-Kuo
Abstract: In this study, rotating-cathode electrodeposition was performed to deposit 30 μ m thick CoMnP films on various substrate materials at room temperature. The electrodeposition configuration and parameters realized a constant current efficiency of about 95%, which was under activation control rather than mass-transport control. Compositional analysis indicated that the deposited thick films were Co-rich with a Co content 92–95 wt.%, regardless of deposition parameters. X-ray diffraction revealed that cathode rotation physically altered the preferred orientation of Co crystallites. The texture of Co crystallites changed with the cathode rotational speed from distinct hexagonal close-packed (HCP) (002) to a heterogeneous phase mixture of HCP (110) and face-centered cubic (FCC) (220). The substrate materials physicochemically affected the relationship between rotational speed and microstructural evolution. The microstructural texture changed nonlinearly with the cathode rotational speed when the films were deposited on catalytic substrate materials, suggesting a substantial influence of the substrate activation nature. Due to magnetocrystalline anisotropy, the resultant films exhibited hard magnetic properties while depositing at the optimal cathode rotational speed. Stationary-cathode electrodeposition resulted in rough CoMnP films with Co grains of 8–18 nm and high Mn content. These films exhibited unique in-plane magnetic properties compared with the films deposited with electrolyte agitation. This study is the first to investigate the combined effects of cathode rotational speed and the activation nature of substrates on the growth behavior of electrodeposited Co-rich CoMnP thick films. The results can be extended to electrodeposition of other Co-based alloys, such as CoP, CoNiP, CoWP, CoPtP, and CoNiMnP.